Epidemiological analysis of influenza vaccination coverage in Pudong New Area, Shanghai (2013-2023): Implications for influenza vaccination strategies - Pengfei Deng; Caoyi Xue; Tian Yang; Bo Zheng; Wenmin Liu; Laibao Yang; Yi Fei (Human Vaccines & Immunotherapeutics)
Seasonal influenza remains a significant public health concern globally, with annual vaccinations as the most effectively preventive measure. This study examines influenza vaccination coverage rates across different age groups in Pudong New Area, Shanghai, China, from 2013 to 2023. This study extracted influenza vaccination data from the Shanghai Immunization Planning Information System (SIPIS) of the Center for Disease Control and Prevention Shanghai’s Pudong New Area from 2013 to 2023. The analysis utilized weighted linear regression to compare vaccination rates over the study period. From 2013 to 2023, a cumulative total of 1,421,295 influenza vaccinations were administered in Pudong New Area, with the quadrivalent inactivated influenza vaccines (IIV4) and trivalent inactivated influenza vaccines (IIV3) comprising 56.8% and 42.9%, respectively. The overall average influenza vaccine coverage rate was 2.27% (95% CI: 2.26, 2.28). The 0–4 years group exhibited the highest average annual coverage rate of 22.52% (95% CI: 22.47, 22.57) among different age groups, in stark contrast to that of the 20–24 years age group, which had the lowest at 0.32% (95% CI: 0.31, 0.33). In terms of repeat vaccinations, a significant majority (86.87%) of recipients received only 1–2 doses, while just 13.13% received 3 or more doses. Although influenza vaccination coverage among preschool children in Pudong New Area is relatively high, it falls significantly short of WHO recommendations. Enhance the level of awareness of influenza vaccine among adults and provide a free influenza vaccination strategy for specific groups such as doctors, which is helpful to increase influenza vaccination rates among populations.